Pendampingan restorasi hukum pernikahan siri pada masyarakat pesisir Tendas di Desa Mojosari Kabupaten Jember - Ainiyah, Qurrotul; Zaman, Ahmad Zuhairuz; Wulandari, Yunita (PERDIKAN (Journal of Community Engagement), 2025)
Based on field observation data, 62.96% of the coastal community of Tendas tend to engage in nikah siri (unregistered marriage) due to low awareness of administrative legal requirements. This community service program aims to carry out legal restoration to reduce the negative impacts of nikah siri, while ensuring legal protection and administrative rights for 17 women involved in unregistered marriages and their children. Using a Participatory Action Research (PAR) approach, this program emphasizes the active participation of the Tendas coastal community in addressing issues related to nikah siri. The program's results reveal three main findings. First, the Tendas coastal community is a relatively isolated community that tends to practice nikah siri due to limited understanding of the risks of unregistered marriage, low educational attainment, weak economic conditions, early marriage practices, and conservative and stubborn attitudes. Second, the community service actions were implemented through focus group discussions (FGDs), training on low-cost marriage registration procedures, the establishment of the Sakinah Mawaddah wa Rahmah (SAMAWA) Family Post, and assistance with the isbat nikah (marriage legalization) process. Third, the legal restoration outcomes in the Tendas community encouraged the legalization of unregistered marriages through isbat nikah, enhanced community legal education, and strengthened the roles of traditional and religious leaders in promoting official marriage registration. Overall, this community service program successfully increased legal awareness among the Tendas coastal community and expanded access to administrative protection through legally registered marriages.[Berdasarkan data observasi lapangan, 62,96% masyarakat pesisir Tendas cenderung melakukan pernikahan siri karena rendahnya kesadaran terhadap hukum administrasi. Pengabdian ini bertujuan melakukan restorasi hukum untuk mengurangi dampak negatif pernikahan siri, sekaligus menjamin perlindungan hukum dan hak administratif bagi 17 perempuan pelaku nikah siri serta anak-anak mereka. Dengan pendekatan Participatory Action Research (PAR), pengabdian ini menekankan partisipasi aktif masyarakat pesisir Tendas dalam menyelesaikan permasalahan nikah siri. Hasil pengabdian menunjukkan tiga temuan utama. Pertama, masyarakat pesisir Tendas merupakan komunitas yang relatif terisolasi dan cenderung melakukan nikah siri akibat kurangnya pemahaman terhadap risiko perkawinan siri, rendahnya tingkat pendidikan, lemahnya kondisi ekonomi, praktik pernikahan dini, serta sikap kolot dan keras kepala. Kedua, aksi pengabdian dilakukan melalui kegiatan focus group discussion (FGD), pelatihan prosedur pencatatan pernikahan berbiaya minimal, pembentukan Posko Keluarga Sakinah Mawaddah wa Rahmah (SAMAWA), serta pendampingan proses isbat nikah. Ketiga, hasil restorasi hukum pernikahan siri di masyarakat Tendas mendorong legalisasi pernikahan melalui isbat nikah, meningkatkan edukasi hukum masyarakat, serta memperkuat peran tokoh adat dan tokoh agama dalam mendorong pencatatan pernikahan secara resmi. Secara keseluruhan, pengabdian ini berhasil meningkatkan kesadaran hukum masyarakat pesisir Tendas serta membuka akses yang lebih luas terhadap perlindungan administratif melalui pencatatan pernikahan yang sah.]